1992
DOI: 10.1111/j.1365-2222.1992.tb03085.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of azelastine on the early allergic response

Abstract: To study the effect of azelastine on the immediate reaction to nasal allergen challenge, we performed a double blind, placebo-controlled cross-over clinical trial. Thirteen subjects with seasonal allergic rhinitis underwent nasal challenge with antigen 4 hr after a single oral 2 mg dose of azelastine. The response was monitored by counting the number of sneezes and by measuring the levels of histamine, prostaglandin D2, immunoreactive sulphidopeptide leukotrienes, kinis and TAME-esterase activity in recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The present results indicate that azelastine, a histamine-1 receptor antagonist, can inhibit the secretion of proinflammatory cytokines IL-6, IL-8 and TNF-α more efficiently than histamine or tryptase. Inhibitory effects of azelastine had been reported in asthma and nasal allergy [8], as well as on the release of TNF-α from rat basophilic leukemia cells [9]and human leukemic mast cells [12]. Histamine-1 receptor antagonists had previously been shown to inhibit mast cell granule-stored mediators [7], as well as cytokine release from human leukemic mast cells (HMC-1) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results indicate that azelastine, a histamine-1 receptor antagonist, can inhibit the secretion of proinflammatory cytokines IL-6, IL-8 and TNF-α more efficiently than histamine or tryptase. Inhibitory effects of azelastine had been reported in asthma and nasal allergy [8], as well as on the release of TNF-α from rat basophilic leukemia cells [9]and human leukemic mast cells [12]. Histamine-1 receptor antagonists had previously been shown to inhibit mast cell granule-stored mediators [7], as well as cytokine release from human leukemic mast cells (HMC-1) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Certain histamine-1 receptor antagonists have variable antiallergic effects [7]. Azelastine has been shown to inhibit the early allergic response [8]and tumor necrosis factor-α (TNF-α) secretion from basophil leukemia cells [9]. However, the effect of azelastine on the release of proinflammatory cytokines from human cord blood-derived cultured mast cells (hCBMC) has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other studies have shown that treatment with azelastine HCl also decreased LTB4, LTC4 and LTD4 levels. 26,27 Treatment with azelastine HCl has been demonstrated to cause a significant decrease (P  0.05) in Substance P and kinin levels. 26,27 Studies investigating the effect of azelastine HCl on mast cells have demonstrated decreased release of inflammatory cytokines and inhibition of tumor necrosis factor alpha.…”
Section: -24mentioning
confidence: 99%
“…26,27 Treatment with azelastine HCl has been demonstrated to cause a significant decrease (P  0.05) in Substance P and kinin levels. 26,27 Studies investigating the effect of azelastine HCl on mast cells have demonstrated decreased release of inflammatory cytokines and inhibition of tumor necrosis factor alpha. [27][28][29] In a double-blind study in AR patients, a significant decrease in neutrophils and eosinophils along with decreased expression of intercellular adhesion molecules was observed.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation